Constitutions of the world - Maddex, Robert L. 1942-; Gale Group (Washington, D.C. CQ Press, 2008)
Offers entries that survey constitutions from 100 nations around the world. Provides an historical overview for each country emphasizing legal and constitutional development.
Electronic reproduction.
Keywords: Constitutional law; Constitutional history; Electronic books